Nonconvex Costs and the Behavior of Inventories - Ramey, Valerie A. (Journal of Political Economy, 1991)
This paper explores one possible explanation for the apparent excess volatility of production relative to sales: nonconvexities in the technology facing firms. It is shown that if firms operate in a region of declining marginal costs, then small shifts in demand can cause production to jump substantially. Estimates for six production-to-stock industries as well as the automobile industry suggest that all these industries behave as if they were operating in the region of nonconvex costs. The results have important implications not only for inventory investment but also for the cyclical behavior of productivity and prices.